2020
DOI: 10.1038/s41598-020-78141-4
|View full text |Cite
|
Sign up to set email alerts
|

Mucin-2 knockout is a model of intercellular junction defects, mitochondrial damage and ATP depletion in the intestinal epithelium

Abstract: The disruption of the protective intestinal barrier—the ‘leaky gut’—is a common complication of the inflammatory bowel disease. There is limited data on the mechanisms of the intestinal barrier disruption upon low-grade inflammation characteristic of patients with inflammatory bowel disease in clinical remission. Thus, animal models that recapitulate the complexity of chronic intestinal inflammation in vivo are of particular interest. In this study, we used Mucin-2 (Muc2) knockout mice predisposed to colitis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 98 publications
1
40
0
2
Order By: Relevance
“…In recent years, it has become clear that inflammatory cytokines can regulate genes involved in glucose and lipid metabolism, affecting overall energy homeostasis [ 36 ]. In agreement with this, clinical and animal studies revealed that chronic inflammation is associated with reduced energy metabolism and strong mitochondrial damage, which results in reduced ATP production in the intestinal epithelium [ 37 , 38 , 39 , 40 ]. In turn, ATP depletion triggers intestinal barrier impairment and worsens the course of colitis [ 41 ].…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…In recent years, it has become clear that inflammatory cytokines can regulate genes involved in glucose and lipid metabolism, affecting overall energy homeostasis [ 36 ]. In agreement with this, clinical and animal studies revealed that chronic inflammation is associated with reduced energy metabolism and strong mitochondrial damage, which results in reduced ATP production in the intestinal epithelium [ 37 , 38 , 39 , 40 ]. In turn, ATP depletion triggers intestinal barrier impairment and worsens the course of colitis [ 41 ].…”
Section: Introductionmentioning
confidence: 53%
“…However, mitochondria are not the only membranous organelles that alter shape and physiology upon colitis. Our previous study, in addition to reports by other authors, revealed the abnormal shape of multiple membranous organelles, including mitochondria, endoplasmic reticulum (ER) and Golgi apparatuses, and cellular and nuclear membranes during inflammation [ 37 , 38 , 39 , 45 , 46 , 47 ]. These indicate that membrane-forming phospholipids may be substantially deregulated upon colitis, which is further supported by experimental data [ 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Mucin 2 (MUC2), an important secretory mucin, is the main structural component of mucus gel in the intestine (Johansson and Hansson 2016). Muc2 knockout (Muc2 −/− ) mice lack a functional mucus layer and exhibit destruction of the duodenal mucosal barrier and increased intestinal permeability (Borisova et al 2020;Gao et al 2016). These studies suggest that mucus has a critical role in maintaining the duodenal mucosal barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Muc3 and Muc2 genes were significantly decreased in desensitized animals. In studies on Muc2 knockout animals, increased intestinal permeability has been shown to triggers a cascade of events leading to secondary organ inflammation and translocation of bacterial metabolites and bacteria per se leading to sepsis 21,22 . Different goblet cell markers (Cdx2, Dll1, Foxa2, Tff3, Dll4, Vamp8, Prkd1, and Foxa3) and Fcgbp were significantly decreased in desensitized animals.…”
Section: Discussionmentioning
confidence: 99%